The phantom of the cinema : character in modern film - Michaels, Lloyd (State University of New York Press, 1998)
Films discussed include Jules and Jim, Escape from Alcatraz, The day of the jackal, Reservoir dogs, Persona, The magician, House of games, Nosferatu: a symphony of horror, Nosferatu: the vampyre, Reilly: ace of spies, The mystery of Kaspar Hauser, The thin blue line, Lacombe, Lucien, Daddy Nostalgia, Mephisto, Badlands, Days of Heaven, Five Easy Pieces, and The lacemaker.
Keywords: Characters and characteristics in motion pictures.; Personnages au cinéma.; PERFORMING ARTS -- Film & Video -- Reference.; Characters and characteristics in motion pictures